Antimicrobial activities of Aloe vera rind extracts against plant pathogenic bacteria and fungi - Kankamol, Chantana; Srikam, Wichai; Chumsiriwong, Kanyapat (Agriculture and Natural Resources, 2021)
Leaves of Aloe vera contain useful substances. Aloe vera gel is used as a component of products, but the rind is discarded as waste despite having more phenol and flavonoid than the gel. The rind has substances with desirable functions, especially antimicrobial and antioxidant activities. The antimicrobial activities were examined of rind extracts against plant pathogenic bacteria: Ralstonia solanacearum and Xanthomonas axonopodi pv. citri and fungi: Colletotrichum gloeosporioides and Fusarium oxysporum. The antimicrobial activities of methanol, ethyl acetate and n-hexane of the rind extracts were tested against these bacteria and fungi. Values were determined for the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The MIC values of the methanol extract against R. solanacearum and X. axonopodis pv. citri were 25 mg/mL and 62.5 mg/mL, respectively, and the MBC values were 50 mg/mL and 125 mg/mL, respectively. The inhibition zones against the two bacteria were positively correlated with the concentration. At 15 mg/mL and 25 mg/mL, the methanol extracts had mean (± SD) values of mycelial growth inhibition against F. oxysporum of 30.85±1.46% and 54.70±1.64%, respectively, and 50.95±0.90% and 62.39±1.08%, respectively, against C. gloeosporioides. The inhibition percentage of mycelial growth increased with increasing concentration. The extracts had higher activity against C. gloeosporioides than F. oxysporum. At the same concentration, the methanol extract had the highest inhibition percentage of mycelial growth, followed by ethyl acetate and n-hexane. The results indicated that rind extracts could be utilized as phytochemical products to inhibit certain bacteria and fungi.